Causes of unspent municipal infrastructure grant in the Capricorn District Municipality : case of two selected local municipalities - Maake, Khomotso Rahab (My University, 2017)
In 1994 the South African democratically elected government inherited one of the most inequitable access to basic service between rural and urban communities. Rural people used to live without access to basic services such as water, electricity, roads and sanitation facilities. South African government established the Municipal Infrastructure Investment Framework as the national Strategic Plan to outline the extent of basic infrastructure backlogs and to come up with strategies to improve basic service provision to the poor citizens. The Municipal Infrastructure Grant (MIG) is a municipal infrastructure funding which combines all the existing capital grants for municipal infrastructure into a single consolidated grant. MIG is aimed at assisting the poor to gain access to infrastructure. MIG funding can only be used for infrastructure for basic services. Polokwane local municipality and Blouberg local municipality are the beneficiaries of MIG. The purpose of the study was to investigate the causes of unspent Municipal Infrastructure Grants in Polokwane and Blouberg local municipalities. An extensive literature review has been undertaken to gather information regarding unspent Municipal Infrastructure Grants in the two municipalities in the Capricorn District; Polokwane and Blouberg local municipalities. The study provides an investigation on how Polokwane and Blouberg local municipalities monitor the Municipal Infrastructure funding. The study further investigate the capacity of the municipalities to implement MIG, and whether these municipalities have the capacity to effectively utilise the MIG for efficient and effective service delivery. The researcher utilised a qualitative approach to collect data through interview schedule. A satisfactory response rate of 98% was obtained. The results indicated that Polokwane and Blouberg local municipalities are capacitated to implement and to monitor MIG. However, the municipalities often spend less than the budgeted MIG, as a result progress in the access to basic services is hindered. The failure to adequately spend the MIG by these municipalities is due to the fact that there is poor planning and a lot of political interference in the Supply Chain Management processes. The study recommended that managers should do proper planning beforehand, avoid late appointment of service providers and make references on the service providers they appoint to avoid disputes from members of the community. The study further recommended that Polokwane and Blouberg local municipalities should do proper consultation of the project, budget accordingly, and appoint companies that will produce positive end results with value for money. The study recommended that political office bearers should not interfere in the supply chain management processes.
Thesis (MPA.) -- University of Limpopo, 2017
Keywords: Rural communities; Urban communities; Municipal infrastructure framework; Municipal infrastructure grant; Access to basic services; Local finance -- Law and legislation --South Africa; Municipal finance -- South Africa; Municipal budgets -- Law and legislation